Electrical Conductivity and Strong Luminescence in Copper Iodide Double Chains with Isonicotinato Derivatives. Issue 48 (6th October 2015) - Hassanein, Khaled; Conesa‐Egea, Javier; Delgado, Salome; Castillo, Oscar; Benmansour, Samia; Martínez, José I.; Abellán, Gonzalo; Gómez‐García, Carlos J.; Zamora, Félix; Amo‐Ochoa, Pilar
Abstract: Direct reactions between CuI and isonicotinic acid (HIN) or the corresponding esters, ethyl isonicotinate (EtIN) or methyl isonicotinate (MeIN), give rise to the formation of the coordination polymers [CuI(L)] n with L=EtIN (1 ), MeIN (2 ) and HIN (3 ). Polymers1 –3 show similar structures based on a CuI double chain in which ethyl‐, methyl isonicotinate or isonicotinic acid are coordinated as terminal ligands. Albeit, their supramolecular architecture differs considerably, affecting the distances and angles of the central CuI double chains and thereby their physical properties. Hence, the photoluminescence shows remarkable differences;1 and2 show a strong yellow emission, whereas3 displays a weak emission; and1 and2 are semiconductors with moderate room temperature conductivities, whereas3 has increased electrical conductivity up to 3×10 −3 S cm −1 . Additionally, 1 and2 present an irreversible transition to a highly conducting phase with a conductivity almost 4 orders of magnitude higher and a quasi‐metallic behaviour. Thermogravimetric analysis (TGA) coupled to a mass spectrometer and magnetic measurements point to a partial thermally induced oxidation of the carboxylate groups of the ligands with Cu I to Cu 0 reduction. DFT calculations have been carried out to rationalise these observations. Abstract : In chains : Coordination polymers obtained by direct reactions between CuI and isonicotinic acid or methyl/ethyl isonicotinato esters show a structure based on a CuI double chain with a rather different supramolecular architecture, which affects the distances and angles of the central chain. These structural variations modify both the emission and electrical properties. DFT calculations have been carried out to rationalise these observations.